Physicochemical characteristics of goat “buchada” added with meat from discarded animals - COSTA, Roberto Germano; OLIVEIRA, Jhonathas Guedes de; SOUSA, Solange; SILVA, Fábio Anderson Pereira da; BELTRÃO FILHO, Edvaldo Mesquita; CRUZ, George Rodrigo Beltrão da; RIBEIRO, Neila Lidiany (Food Science and Technology, 2025)
The aim of this research was to evaluate the effects of adding meat from waste animals on the physicochemical and sensory characteristics of goat buchada. Four treatments were prepared: one control (no meat added) and three with 15, 30, and 50% of the viscera replaced by meat from waste goats. Eight goat buchadas, each weighing approximately 70 g, were used for the sensory analysis. The variables ashes, lipids, and proteins showed significant differences (p < 0.05) depending on the addition of goat meat to the buchada. The factors meat addition and storage time had a significant effect (p < 0.05) on 2‐thiobarbituric acid reactive (TBAR) values, so increasing the levels of meat in the buchada decreased the levels of lipid oxidation, while increasing the storage time increased this same parameter in the buchada. The sensory attributes of the smell of buchada, the smell and taste of goat meat, and juiciness showed a significant difference (p < 0.05) depending on the addition of goat meat to the buchada. Three main components were needed to explain 71.15% of the variation in the data relating to physicochemical analysis and sensory attributes. In conclusion, reformulating buchada by partially incorporating meat from waste goats improves the nutritional and sensory quality of the product, as well as adds value to the meat of waste animals.